PENGEMBANGAN E-MODUL DENGAN PENDEKATAN STEAM-PJBL PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS SOCIO SCIENTIFIC ISSUES UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR - Siregar, Sofiyan (Attadib: Journal of Elementary Education, 2024)
Scientific creativity must be trained to elementary school students from an early age, as a provision for students to have creative thinking skills and train student creativity. The purpose of this study is to increase student creativity by applying the STEAM (Science, Technology, Engineering, Art, Mathematics) learning approach based on PjBL (Project Based Learning) by linking socio scientific issues in learning. This study used Research and Development (R&D) design with a 4-D model. The subjects in this study were 26 grade IV students of SDN Pakintelan 01 Gunungpati, Semarang. Data collection techniques in this study are observation, interviews, questionnaires, and tests. This research data analysis technique includes analysis of media validation results, media practicality data analysis, classical completeness analysis, and analysis of student test results. The results of this study include: 1) e-module with steam-pjbl approach based on socio scientific issues; 2) e-module with steam-pjbl approach based on socio scientific issues is very valid with an overall average value of media validation test of 0.93 and e-module developed of very practical quality with an overall average value of media practicality test of 0.89%; 3) the classical completeness value of the media effectiveness test obtained high effectiveness results with a percentage of 0.88%; 4) The e-module is declared effective with the difference between the pretest and posttest scores, as well as the results of the n-gain test with an average of 0.60 classified as medium